Cognitive control adjustments and conflict adaptation in major depressive disorder. (4th June 2013) - Clawson, Ann; Clayson, Peter E.; Larson, Michael J.
Abstract Individuals with major depressive disorder (MDD) show alterations in the cognitive control function of conflict processing. We examined the influence of these deficits on behavioral and event‐related potential (ERP) indices of conflict adaptation, a cognitive control process wherein previous‐trial congruency modulates current‐trial performance, in 55 individuals with MDD and 55 matched controls. ERPs were calculated while participants completed a modified flanker task. There were nonsignificant between‐groups differences in response time, error rate, and N2 indices of conflict adaptation. Higher depressive symptom scores were associated with smaller mean N2 conflict adaptation scores for individuals with MDD and when collapsed across groups. Results were consistent when comorbidity and medications were analyzed. These findings suggest N2 conflict adaptation is associated with depressive symptoms rather than clinical diagnosis alone.